2023
DOI: 10.15252/emmm.202216775
|View full text |Cite
|
Sign up to set email alerts
|

Pathological variants in TOP3A cause distinct disorders of mitochondrial and nuclear genome stability

Abstract: Topoisomerase 3a (TOP3A) is an enzyme that removes torsional strain and interlinks between DNA molecules. TOP3A localises to both the nucleus and mitochondria, with the two isoforms playing specialised roles in DNA recombination and replication respectively. Pathogenic variants in TOP3A can cause a disorder similar to Bloom syndrome, which results from bi-allelic pathogenic variants in BLM, encoding a nuclear-binding partner of TOP3A. In this work, we describe 11 individuals from 9 families with an adult-onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…The ability of Mirin to counteract the mtDNA breakage caused by mitochondrially targeted TOP3A (Figure 4) provides interesting insight into the formation of the OriH-OriL fragment in the MGME1 KO cells and mtDNA replication in general. As explained, besides resolving the hemicatenanes formed during replication termination (Nicholls et al, 2018), TOP3A also removes the torsional stress during mtDNA replication (Hangas et al, 2022;Erdinc et al, 2023). It is perfectly plausible that due to the small size of the mitochondrial genome the nicking action for this function also occurs on the NCR, occasionally resulting in the breakage of the newly replicated part (Figure 4D), especially when H-strand replication is paused for a prolonged time at OriL (Torregrosa-Munumer et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The ability of Mirin to counteract the mtDNA breakage caused by mitochondrially targeted TOP3A (Figure 4) provides interesting insight into the formation of the OriH-OriL fragment in the MGME1 KO cells and mtDNA replication in general. As explained, besides resolving the hemicatenanes formed during replication termination (Nicholls et al, 2018), TOP3A also removes the torsional stress during mtDNA replication (Hangas et al, 2022;Erdinc et al, 2023). It is perfectly plausible that due to the small size of the mitochondrial genome the nicking action for this function also occurs on the NCR, occasionally resulting in the breakage of the newly replicated part (Figure 4D), especially when H-strand replication is paused for a prolonged time at OriL (Torregrosa-Munumer et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…However, it is likely that these effects are interconnected as one can imagine that reduced D-loop formation should increase mtDNA supercoiling. It can also well be that the relaxation activity of TOP3A is not the direct target for Mirin, as different pathological mutations in the enzyme can produce relatively different outcomes in terms of their molecular effects as well as pathology (Erdinc et al, 2023). Future research will hopefully decipher the inconsistencies in the reported Mirin targets as well as increase our understanding about the relationships of mtDNA replication termination, 7S DNA and mtDNA topology.…”
Section: Discussionmentioning
confidence: 99%
“…It can alter DNA topology by creating temporary breaks in the DNA backbone [ 34 ]. Notably, TOP3A dysfunction may affect the stability of the nuclear or mitochondrial genome [ 35 ]. SRC is an intracellular non-receptor tyrosine kinase that plays a crucial role in regulating various biological processes associated with tumor proliferation, migration, invasion, and angiogenesis [ 36 ] Studies have shown aberrant activation or expression of SRC kinases in various tumor tissues, including prostate, breast, lung, and colorectal cancers [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic progressive external ophthalmoplegia (CPEO) plus syndrome due to pathogenic biallelic missense variants in the TOP3A gene may be associated with reduced TOP3A activity, affecting its mitochondrial functions [ 134 , 139 ]. Based on the correlation of the disease characteristics and positions of the different pathological TOP3A variants on the crystal structure of TOP3A N-terminal domains, it has been proposed that variants with more severe effects on TOP3A catalytic activity could lead to Bloom syndrome-like disorder, while variants expected to have less severe impact on TOP3A catalytic activity could result in adult-onset mitochondrial disease [ 140 ].…”
Section: Physiological Functions Of Type Ia Topoisomerasesmentioning
confidence: 99%